ULTIMATE STRENGTH OF BOX BEAMS STRENGTHENED IN DIFFERENT TOQUE-TO-SHEAR RATIOS WITH CFRP SHEETS (Malaysian Journal of Civil Engineering, 2018)
An experimental investigation and derived equations of ultimate torque on reinforced concrete (RC) box beams strengthened by carbon fiber-reinforced-polymer (CFRP) sheets subjected to combinedl torsion and shear have been carried on research. In this experiment, eight box beams were cast and separated into two groups according to two different torque-to-shear ratios (i.e., 1.597 and 2.556). Three box beams from each group strengthened by CFRP in different configurations and one control box beam were tested. The main parameters of this experiment were the different ratios and configurations, including U-jacket layers and U-jacket strips with or without longitudinal strips. The cracking pattern, failure mode, effect of wrapping schemes, torsional capacity, and behavior of the various torque-to-shear ratios were studied in detail. In terms of the variable-angle truss model and mode-2 type of failure as well as shear flow and equilibrium of forces and moment, the equations for calculating the ultimate torque of the box beams strengthened by CFRP sheets were derived. According to existing experimental results, the experimental and calculational values show a close agreement